EFEK HEPATOPROTEKTIF EKSTRAK METANOL JAHE MERAH (Zingiber officinale Roscoe) PADA MENCIT JANTAN YANG DIINDUKSI CCl4 - Bachri, Moch Saiful (Universitas Ahmad Dahlan, 2011)
MeOH extract of Zingiber officinale Roscoe (ZO) were investigated forhepatoprotective effect at the doses (p.o) of 100 and 200 mg/kg body weight using CCl4induction method. Male Swiss mouse (25±1,5 g) were treated with ZO doses 100 and200 mg/kg bw and Sillymarin (100 mg/kg bw) for two week before treatment with asingle dose of CCl4, 0.5 ml/kg bw, intraperitoneally. The mouse were sacrifactivity ofSGPT-SGOT. The study showed the activity of SGPT of MeOH extract of ZO doses 100mg/kg bw and 200 mg/kg bw, Sillymarin, control and normal groups are (34,51±5,34)(27,38±4,28) (27,26±1,06) (36,61±1,87) dan (25,37±2,01I) U/L. respectively. Whilethe activity of SGOT of MeOH extract of ZO doses 100 mg/kg bw and 200 mg/kg bw,Sillymarin, control and normal groups are (88,88±0,94) (83,88±3,91) (83,99±7,24)(92,97±8,16) (82,99±3,97) U/L.respectively. MeOH extract of ZO dose 200 mg/kg BWand Sillymarinsignificantly (p < 0,05) decrease the activities two enzymes (SGPT andSGOT). The results showed MeOH extract Zingiber officinale Roscoe hashepatoprotective effect.